2000
DOI: 10.1021/ie990746+
|View full text |Cite
|
Sign up to set email alerts
|

A Simulation of the Accumulation of Solid Particles in Coal Liquefaction Reactors Based on the NEDOL Process

Abstract: A direct coal liquefaction plant was constructed in Kashima, Japan, based on the concept of “NEDOL Process”, and successfully processed 150 tons of Tanitorarum coal per day during 1997−1998. The plant was equipped with three reactors:  1 m in diameter and 11.8 m in length, connected in series. During the operation, solid particles were accumulated mainly in the first reactor. Slurry samples were directly removed from the reactors, and size distributions of solid particles were determined. Two types of particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Quantitative Analysis of Deposits. There have been several studies related to behavior of inorganic matter in the liquefaction process. , In these studies, inorganic matter in deposits, liquefaction residue, and extract solution after solid−liquid separation 10,11 were characterized. However, no systematic and quantitative analysis of the deposits in the liquefaction plant has been made so far, and therefore details of the mechanism of deposit formation have not been understood yet.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative Analysis of Deposits. There have been several studies related to behavior of inorganic matter in the liquefaction process. , In these studies, inorganic matter in deposits, liquefaction residue, and extract solution after solid−liquid separation 10,11 were characterized. However, no systematic and quantitative analysis of the deposits in the liquefaction plant has been made so far, and therefore details of the mechanism of deposit formation have not been understood yet.…”
Section: Resultsmentioning
confidence: 99%
“…The operation was almost successful; however, it was reported that some problems occurred related to the solid deposition in several units in the facility. The deposit reduced the effective volume of the reactor and connecting pipe, resulting in a significant pressure drop and decrease of residence time of the slurry in the reactor. There have been several reports about the deposits in coal liquefaction plants. In these studies, the deposits in coal liquefaction plant were analyzed qualitatively. For example, Aramaki et al analyzed the carbonaceous and inorganic solids in deposits of a 150 t/day pilot plant.…”
Section: Introductionmentioning
confidence: 99%
“…Although demonstrating the principles of coal liquefaction, the disadvantages of the NEDOL process rendered it impractical for wide-scale implementation. The catalyst can be deactivated through the deposition of coke and ash onto the catalyst surface, and the presence of minerals in the reaction mixture can cause accumulation of solid particles and eventual deterioration of equipment such as liquefaction reactors, separators, and pipelines. , Furthermore, relatively high temperatures and hydrogen pressures were required, leading to a high cost for coal liquefaction.…”
Section: Introductionmentioning
confidence: 99%
“…This technique could find application in waste treatment, metal oxide reduction, energy production, petrochemical, and other fluid−solid processes. It could contribute substantially to surface treatment of medical tablets, production of carbon nanotubes, , sulfur capture in energy production, solids and catalyst attrition and modification, and degradation of metal oxide used as oxygen carrier chemical vapor deposition, , foodstuff and grain conditioning, and particle distributions in reactors .…”
Section: Introductionmentioning
confidence: 99%